Midbrain dopaminergic neurons generate calcium and sodium currents and release dopamine in the striatum of pups - Ferrari, Diana C.; Mdzomba, Baya J.; Dehorter, Nathalie; Lopez, Catherine; Michel, François J.; Libersat, Frédéric; Hammond, Constance (Frontiers in Cellular Neuroscience, 2012)
Midbrain dopaminergic neurons (mDA neurons) are essential for the control of diverse motor and cognitive behaviors. However, our understanding of the activity of immature mDA neurons is rudimentary. Rodent mDA neurons migrate and differentiate early in embryonic life and dopaminergic axons enter the striatum and contact striatal neurons a few days before birth, but when these are functional is not known. Here, we recorded Ca2+ transients and Na+ spikes from embryonic (E16-E18) and early postnatal (P0-P7) mDA neurons with dynamic two photon imaging and patch clamp techniques in slices from tyrosine hydroxylase-GFP mice, and measured evoked dopamine release in the striatum with amperometry. We show that half of identified E16-P0 mDA neurons spontaneously generate non-synaptic, intrinsically-driven Ca2+ spikes and Ca2+ plateaus mediated by N- and L-type voltage-gated Ca2+ channels. Starting from E18-P0, half of the mDA neurons also reliably generate overshooting Na+ spikes with an abrupt maturation at birth (P0 = E19). At that stage (E18-P0), dopaminergic terminals release dopamine in a calcium-dependent manner in the striatum in response to local stimulation. We propose that the intrinsic spontaneous activity of mouse mDA neurons may impact the development/activity of the striatal network from birth.